Laser Fabrication of Bioinspired Graphene Surfaces With Superwettability - Ma, Zhuo-Chen; Li, Chun-He; Hu, Xin-Yu; Han, Bing; Zhang, Yong-Lai; Chen, Qi-Dai; Sun, Hong-Bo (Frontiers in Chemistry, 2020)
The past decades have seen growing research interest in developing efficient fabrication techniques for preparing bioinspired graphene surfaces with superwettability. Among the various fabrication methods, laser fabrication stands out as a prominent one to achieve this end and has demonstrated unique merits in the development of graphene surfaces with superwettability. In this paper, we reviewed the recent advances in this field. The unique advantages of laser fabricated graphene surfaces have been summarized. Typical graphene surfaces with superwettability achieved by laser fabrication, including superhydrophobic graphene surfaces, oil/ water separation, fog collection, antibacterial surfaces, surface enhanced Raman scattering (SERS), and desalination, have been introduced. In addition, current challenges and future perspectives in this field have been discussed. With the rapid progress of novel laser physical/ chemical fabrication schemes, graphene surfaces with superwettability prepared by laser fabrication may undergo sustained development and thus contribute greatly to the scientific research and our daily life.